2009
DOI: 10.1902/jop.2009.080309
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bone Decortication in Enhancing the Results of Guided Bone Regeneration: A Literature Review

Abstract: There is conflicting information and not enough clinical trials to make a definitive determination as to the merits of bone decortication prior to GBR procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 61 publications
1
48
1
4
Order By: Relevance
“…A recent review paper found conflicting information on the role of bone decortication in enhancing outcomes for GBR. The authors suggested the need for clinical trials to elucidate the role of this variable in GBR procedures 30 . Cortical perforations at the recipient site may have enhanced the blood supply coming from the marrow spaces favoring the process of osteogenesis in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…A recent review paper found conflicting information on the role of bone decortication in enhancing outcomes for GBR. The authors suggested the need for clinical trials to elucidate the role of this variable in GBR procedures 30 . Cortical perforations at the recipient site may have enhanced the blood supply coming from the marrow spaces favoring the process of osteogenesis in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…The evidence on the efficacy for cortical perforation (decortication) during GBR procedures in an effort to enhance bone formation remains controversial [142]. Studies have shown that cortical perforations increase the blood supply, facilitate angiogenesis, and allow access for progenitor cells from the bone marrow into the 'chamber' [142] whereas other studies showed that bone formation occurred from a non-injured cortical bone surface and that perforations were not required as they did not increase bone formation [59,81].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cortical perforations increase the blood supply, facilitate angiogenesis, and allow access for progenitor cells from the bone marrow into the 'chamber' [142] whereas other studies showed that bone formation occurred from a non-injured cortical bone surface and that perforations were not required as they did not increase bone formation [59,81]. However, since there are no relevant human clinical studies and the relevant animal studies refer to mandibular defects, where local vascularity is superior to long bones, recommendations for additional bone decortication cannot be made for orthopedic GBR applications [142]. …”
Section: Discussionmentioning
confidence: 99%
“…The benefits of decortication are increased bleeding, access for progenitor cells and blood vessels, interlocking of bone, and spatial relationships of decortications in traditional OS. Prior to lasers, decortication could have only been done mechanically by scalers or dental drills only [63].…”
Section: Decorticationmentioning
confidence: 99%